Investigating the floral and reproductive biology of the endangered microendemic cactus Uebelmannia buiningii Donald (Minas Gerais, Brazil) - Teixeira, Valber Dias (2018)
The Cactaceae are known to be amongst the most endangered plant families of the world due to reduction of their habitats and activities of collectors. As the species of the family are dependent on animals to perform cross pollination, and hence seed production, their population performance may be further negatively affected by interrupted biotic interactions. For efficient conservation of rare species, knowledge on reproductive biology and pollinators is of prime importance. In our study we focused on Uebelmannia buiningii Donald, a microendemic cactus from the Serra Negra State Park, Minas Gerais state, Brazil. During four field expeditions to three localities of the species between September 2012 and September 2013, we measured flowers, detected nectar-guides and osmophores and performed pollen viability tests. We studied the reproductive system of the species using manual self- and cross-pollination tests and observed pollinators. Our results revealed that the flowering period takes place during the dry season, between April and October, and that the diurnal flowers open between 7:00 a.m. and 5 p.m. The flowers are shortly tubular with yellow perianth-segments. We found neither nectar nor nectar-guides, and osmophores appeared as glands within the flower tube. Whereas pollen viability was 90.25%, manual crosspollination tests have shown cross-pollination with gametophytic incompatibility. We observed two bee species visiting the flowers and acting as effective pollinators: Dialictus opacus and Plebeia sp. The combination of low reproductive activity with gametophytic incompatibility, together with the reduced number of individuals in a population and low number of populations, makes the endemic cactus U. buiningii a critically endangered species